Цифровізація агроринку Казахстана - Akhmedyarov, Yerbol (Dr. Viktor Koval, 2019)
Introduction. An increase of the Earth population leads to the necessity to increase food production. To ensure world food security, it is necessary to increase food production compared to the current time by 70%. The solution to this global problem is possible due to the modernization of the economy using digital technologies and artificial intelligence. Despite the fact that Kazakhstan, at present, has significant potential in food production, even its own needs are not fully provided. The article discusses the possibility of digitalization of the agricultural market of Kazakhstan in order to increase the volume of milk production and processing, increasing the competitiveness of dairy products, realization of the export potential and ensuring food security of the country. Aim and tasks. The aim of the study is to justify the need for the adoption of digital technologies in the agricultural market of Kazakhstan. Results. The article discusses the concept of the term "digitalization of the economy" in the world and its spheres of application. Practical examples of digitalization in countries with a developed economic system and the need for their usage in order to transfer to the digital structure of the agricultural market are given. The volumes of milk production in Kazakhstan over the past 3 years are analyzed. The reasons for the incomplete plant capacities of milk processing enterprises and the low level of marketability of dairy farming in Kazakhstan are identified. The rationale is given, that the use of digital technologies and other positive effects associated with their use will contribute to the improvement of the quality of milk. Conclusions. According to the results of the study, the constraints on the development of the dairy industry in Kazakhstan were identified and it was found that most of them can be solved using digital technologies. The solution of these problems is possible with the aid of creation of information platforms and technological re-equipment, conditioned upon organizational, legal and financial support of the state. It was substantiated that the integrated use of digital technologies in the agricultural market of Kazakhstan along the entire product distribution chain from raw milk to sales to the final consumer will help to reduce costs, improve the quality of milk and dairy products, labor productivity, as well as to transform the workforce of the industry.